2023
DOI: 10.1039/d3ee01546g
|View full text |Cite
|
Sign up to set email alerts
|

Cross-linking polymerization boosts the performance of perovskite solar cells: from material design to performance regulation

Xing Yin,
Ziyu Wang,
Yingjie Zhao
et al.

Abstract: Perovskite polycrystalline films with massive grain boundaries (GBs) lead to high defect densities as well as poor environmental stability. Polymers additives provide an effective insight to solve these problems. However,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 200 publications
0
2
0
Order By: Relevance
“…[ 45–49 ] Particularly, perovskite solar cells (PSCs) have revolutionized the solar cell sector with their swiftly improving power conversion efficiency (PCE), now on par with commercialized silicon‐based solar cells. [ 50–58 ] In particular, the stability of PSCs has seen notable advancements, particularly through encapsulation techniques and stability testing tailored for real‐life applications. Developments in defect‐tolerant materials and better ion migration control contribute to enhanced cell longevity [ 59–64 ] ; However, challenges persist, particularly in terms of operational stability under ambient conditions [ 65,66 ] and mechanical stability when designed as flexible devices.…”
Section: Introductionmentioning
confidence: 99%
“…[ 45–49 ] Particularly, perovskite solar cells (PSCs) have revolutionized the solar cell sector with their swiftly improving power conversion efficiency (PCE), now on par with commercialized silicon‐based solar cells. [ 50–58 ] In particular, the stability of PSCs has seen notable advancements, particularly through encapsulation techniques and stability testing tailored for real‐life applications. Developments in defect‐tolerant materials and better ion migration control contribute to enhanced cell longevity [ 59–64 ] ; However, challenges persist, particularly in terms of operational stability under ambient conditions [ 65,66 ] and mechanical stability when designed as flexible devices.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the hysteresis was also suppressed in the target device, as seen in Figure S13. The statistical analysis from 50 individual devices in Figure S14 showed that the PCE, V oc , and FF of target devices were significantly improved with a slight reduction in J sc , which might be attributed to the relatively low conductivity of the residual polymerized HEMA within the film. Figure S15 presents the cross-section SEM images of the control and target perovskite films; we attributed the incomplete coverage at the perovskite/SnO 2 interface to the rapid crystal growth in the pristine perovskite . In contrast, a uniform perovskite film that is closely connected to the underlying SnO 2 was formed for the HEMA-modified perovskites.…”
mentioning
confidence: 99%